2002
DOI: 10.2527/2002.80112862x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary-induced changes of muscle growth rate in pigs: Effects on in vivo and postmortem muscle proteolysis and meat quality1

Abstract: The effects of various growth rates in pigs induced by four different feeding strategies on the activity of the calpain system and on postmortem (PM) muscle proteolysis and tenderness development were studied. An increased growth rate may be caused by an increased protein turnover, which results in up-regulated levels of proteolytic enzymes in vivo that, in turn, possibly will affect PM tenderness development. It can be hypothesized that increased proteolytic activity pre-slaughter will increase the PM tenderi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
73
4
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(91 citation statements)
references
References 37 publications
11
73
4
3
Order By: Relevance
“…A plausible cause for this difference could be the compensatory growth of IC, compared to C and EMG pigs, at the end of the finishing period. Recently, Kristensen et al (2002) and Bee et al (2006) reported that compensatory growth before slaughter is followed by an increased proteolytic potential (m-calpain : calpastatin ratio) and higher tenderization rate.…”
Section: Discussionmentioning
confidence: 99%
“…A plausible cause for this difference could be the compensatory growth of IC, compared to C and EMG pigs, at the end of the finishing period. Recently, Kristensen et al (2002) and Bee et al (2006) reported that compensatory growth before slaughter is followed by an increased proteolytic potential (m-calpain : calpastatin ratio) and higher tenderization rate.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation pertains with the much increased growth rate in the weeks before slaughter, resulting in enhanced protein turnover in vivo, and hence increased proteolysis post mortem (Therkildsen et al, 2004;Lametsch et al, 2006). Compensatory growth has been proposed to have a positive effect on pork tenderness (Kristensen et al, 2002).…”
Section: Meat Qualitymentioning
confidence: 99%
“…Kristensen et al (2002) found a relationship between diet and texture of meat. Also, Cisneros et al (1996) and Smith et al (2002) reported a relationship between feed and the colour of meat.…”
Section: Introductionmentioning
confidence: 97%